Puzzles on mobile devices as a support tool for learning programming fundamentals - Cela, Ingrid (2022)
There is a constant search for more and new tools that help to face the problem that implies fostering motivation to acquire knowledge and develop skills in complex areas or subjects such as programming. One option is serious games, which have become an increasingly used tool in education as a support to the teaching-learning process, helping students to acquire or reinforce the knowledge of the subjects in an entertaining way. With this reference, this work proposes the use of puzzles as help in learning the fundamentals of programming. For this, a prototype of serious game based on puzzles for mobile devices was designed. The prototype was evaluated with the participation of students who were attending a first level of programming. The results of this evaluation were positive, with the participants suggesting that the prototype was attractive and easy to use. This fact allows concluding that the use of puzzles on mobile devices when learning programming for the first time is a valid idea that can support learning.